Clove bud (Syzygium aromaticum L.) polyphenol helps to mitigate metabolic syndrome by establishing intracellular redox homeostasis and glucose metabolism: A randomized, double-blinded, active-controlled comparative study. (November 2022) - Thomas, Jestin; Patel, Anand; Das Sivadasan, Syam; Sreevallabhan, Sheethal; Illathu Madhavamenon, Krishnakumar; Mohanan, Ratheesh
Graphical abstract: Highlights: Influence of Clovinol verses synthetic Glutathione (s-GSH) in metabolic syndrome. Clovinol enhanced Nrf2 and plasma GSH levels by 6-fold compared to s-GSH. Clovinol helps balanced intracellular redox homeostasis. Clovinol modulated glucose and lipid metabolism. Clovinol may help balanced immunity. Abstract: Present randomised double-blinded comparative study investigated the influence of clove buds ( Syzygium aromaticum ) polyphenol extract (Clovinol) in comparison with synthetic glutathione (s-GSH) (250 mg/day for 84 days) on healthy adults (N = 70) characterised with metabolic syndrome (MetS). Outcome measures included plasma concentration of endogenous antioxidants, inflammatory markers, blood sugar and lipid metabolism markers, in addition to haematological and biochemical parameters of safety. Clovinol enhanced the plasma concentration of GSH by 6-fold and offered statistically significant enhancement in Nrf2, antioxidant enzymes and in GSH/GSSG ratio. Treatment with Clovinol also improved FBS, PPG, HbA1c, HOMA-IR and insulin levels indicating modulation of insulin resistance. Moreover, Clovinol caused significant reduction in total cholesterol, triglycerides, LDL and increased HDL, while s-GSH showed no significant effect on blood glucose and lipid metabolism. Clovinol did not show any significant side effects or toxic deviations in haematological and biochemical parameters, but significantly increased the total leukocyte and reduced neutrophil/lymphocyte ratio and inflammatory markers (IL-1β and TNF-α).